Pengembangan Fitur Tampilan Status Dosen Berbasis Raspberry Pi dengan Metode Rapid Application Development (RAD) di Lingkungan Akademik - Hamdana, Elok Nur; Rizky Yunianto, Dika; Eka Apriyani, Meyti (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
The advancement of information technology drives improvements in academic services, including providing fast and transparent access to lecturer attendance status information. This study develops a Raspberry Pi-based lecturer status display to show real-time lecturer attendance. The system is developed using the Rapid Application Development (RAD) method through the stages of data collection, analysis, design, implementation, and testing. Functional testing results show a 98% accuracy rate in data synchronization between the database and the display screen. A questionnaire distributed to 12 lecturers revealed that 86.7% of respondents found the application highly beneficial in quickly and transparently obtaining lecturer attendance information. Thus, this application can enhance efficiency and information transparency in the academic environment